YIDDISH PREFIXED VERBS DESCRIBING THE ACHIEVEMENT OF A LONG-TERM ACTION OR PROCESS - O. V. Bader; K. A. Shishigin (Вестник Кемеровского государственного университета, 2014)
The authors analyze the Yiddish verbs with the prefix derdescribing the achievement of long-term process or action. The paper shows their semantic, word-formative and morphosyntactic characteristics and also demonstrates that Yiddish verbs of this class, remaining German in form, became mostly Slavonic in their semantic and morphosyntactic characteristics.